Topographic hotspots of Southern Ocean eddy upwelling - Yung, Claire Kah-Lei (The Australian National University, 2021)
Upwelling of cold water from the deep ocean to the surface of the Southern Ocean is an important climate process because it facilitates the absorption of a large amount of anthropogenic heat and carbon. Upwelling is mediated by turbulent eddies, which allow water from the mid-depths of the ocean to flow to the surface along a southward and upward pathway. Upwelling was previously conceptualised in a longitudinally-averaged framework, but it has recently been observed to vary in strength with longitude. Near topography, such as underwater mountains and ridges, upwelling is enhanced in so-called topographic hotspots of upwelling. The energetics of processes near topographic hotspots of upwelling remain poorly understood. Furthermore, coarse-resolution models used in climate predictions cannot resolve eddies (and thus upwelling) and instead parameterise their behaviour. Understanding the mechanisms that facilitate upwelling hotspots is hence important, as an accurate physical understanding of eddies is required for improved eddy parameterisations and thus climate predictions. Using a high-resolution (0.1 degree) global ocean sea-ice model, I calculate spatial distributions of upwelling transport and energy conversions associated with the upwelling process. I find that five major topographic hotspots of upwelling, covering less than 30% of the circumpolar longitude range, account for up to 76% of the southward eddy upwelling transport. Maximal eddy kinetic energy is found downstream of the upwelling hotspots by on average 130km, in accordance with sparse observational studies. The mechanisms that create the downstream eddy kinetic energy remain unclear, but my energy conversion analysis can identify which mechanisms proposed in the literature are more plausible. I show that upwelling is highly correlated with an energy conversion associated with baroclinic instability, suggesting that eddy parameterisations that quantify baroclinic energy conversions could be used to improve the simulation of upwelling hotspots in climate models.